2002
DOI: 10.1046/j.1365-2362.2002.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant and inflammatory response of virus‐infected monocytes

Abstract: The procoagulant activity of virus-infected monocytes is TF-dependent. Although influenza infection did not generate a significant reduction in clotting time, the pronounced expression of IL-6 and IL-8 may induce local and/or systemic inflammatory reactions, which may be associated with plaque rupture and atherosclerosis. The lack of production of the anti-inflammatory cytokine IL-10 may even accelerate these processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 59 publications
(90 reference statements)
2
52
0
1
Order By: Relevance
“…Several environmental factors have been identified, such as strong inducers of TF gene expression, including viruses, 44 bacteria, [45][46][47] other microbial pathogens such as cytomegalovirus, Chlamydia pneumoniae, Streptococcus sanguis and Plasmodium falciparum, [48][49][50] endotoxin 51 and oxidative air pollutant particulate matter. 52 In this study, we showed that the G allele in the À603 position is associated with a higher promoter activity than the A allele in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Several environmental factors have been identified, such as strong inducers of TF gene expression, including viruses, 44 bacteria, [45][46][47] other microbial pathogens such as cytomegalovirus, Chlamydia pneumoniae, Streptococcus sanguis and Plasmodium falciparum, [48][49][50] endotoxin 51 and oxidative air pollutant particulate matter. 52 In this study, we showed that the G allele in the À603 position is associated with a higher promoter activity than the A allele in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…A state of chronic alveolitis has been described in mice with ongoing inflammatory response and presence of antigen in lungs for months (up to 1 year) after acute influenza. 29 Bouwman et al 27 recently showed that infection of monocytes by influenza reduced clotting time by 19%. Monocytes produced both interleukin (IL)-6 and IL-8 after infection with influenza (3-to 5-fold higher than with CMV and C. pneumoniae).…”
Section: How Might Influenza Trigger Acute Mi?mentioning
confidence: 99%
“…24 Potential mechanisms may include (1) antigenic cross-reactivity (in our mice, only the plaques, and not the normal arterial segments, were inflamed); (2) an increase in pro-inflammatory, prothrombotic cytokines; (3) endothelial dysfunction; (4) increased plasma viscosity; (5) tachycardia; (6) release of endogenous catecholamines; (7) psychological distress; (8) dehydration leading to hypotension and to hemoconcentration; (9) hypoxemia; (10) demand ischemia; (11) loss of the anti-inflammatory properties of HDL particles; (12) increase in trafficking of macrophages into the arterial wall; (13) pronounced expression of inflammatory cytokines by infected monocytes and reduction in clotting time; and (14) induction of procoagulant activity in infected endothelial cells, reduction in the clotting time, and increase in the expression of tissue factor. 17,[25][26][27][28] In addition to the acute effects, influenza may have indolent and chronic inflammatory consequences in the body. A state of chronic alveolitis has been described in mice with ongoing inflammatory response and presence of antigen in lungs for months (up to 1 year) after acute influenza.…”
Section: How Might Influenza Trigger Acute Mi?mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Cytomegalovirus (CMV) and Chlamydia pneumoniae (Cp) are thought to be involved in the pathogenesis of atherosclerosis and cardiovascular disorders. [9][10][11][12][13][14] It has been shown before that adenoviruses (Ad) are able to infect adipocytes 15,16 and that this is possibly related to the development of obesity. 17,18 Data from studies in animals indicate a possible role for virus infections in the etiology of human obesity.…”
Section: Introductionmentioning
confidence: 99%